COMBINING ABILITY STUDIES FOR YIELD AND FIBER TRAITS IN UPLAND COTTON - S. A. Khan; N. U. Khan; R. Gul; Z. Bibi; I. U. Khan; S. Gul; S. Ali; M. Baloch (Journal of Animal and Plant Sciences, 2015)
Genetic potential and combining ability were studied in 6 × 6 F1 cross of Gossypium hirsutum L. at the University of Agriculture, Peshawar, Pakistan. Six parental genotypes (CIM-446, CIM-496, CIM-499, CIM-506, CIM-554 and CIM-707) and their 30 F1 diallel progenies were grown in a randomized complete block design with three replications. Significant (p≤0.01) differences were observed among the genotypes for bolls per sympodia, bolls per plant, boll weight, seed cotton yield per plant, lint % and lint index. F1 hybrids showed significant increase over parental means for all the traits. Mean squares due to GCA and SCA were highly significant for all the traits. The GCA mean squares were higher than SCA for majority traits which revealed that additive genes controlled the inheritance. Utilization of best general combiners (CIM-446 and CIM-554) as one of the parents produced promising F1 population (CIM-446 × CIM-554, CIM-446 × CIM-496 and CIM-506 × CIM-554) with desirable SCA and mean performance for yield and fiber traits. Therefore, high × low, low × high and in some cases high × high GCA parents showed best performance for majority traits. Correlation of seed cotton yield was significantly positive with yield related traits however, the association was negative with lint %. Additive gene action controlled the inheritance, and selection in above promising hybrids could be used in early segregating generations and in hybrid cotton production to enhance the seed cotton yield.
Keywords: Combining ability; GCA & SCA effects; additive and non-additive gene action; diallel cross; F1 hybrids; upland cotton